Electric field induced, superhydrophobic to superhydrophilic switching in multiwalled carbon nanotube papers - Kakade, Bhalchandra A.; Mehta, Rutvik; Durge, Apurva; Kulkarni, Sneha; Pillai, Vijayamohanan (Nano Letters, 2008)
Superhydrophobic multiwalled carbon nanotube bucky paper, fabricated after ozonolysis, shows fascinating electrowetting behavior, which could be remarkably tuned by changing key solution variables like the ionic strength, the nature of the electrolyte, and the pH of the water droplet. More significantly, the droplet behavior can be reversibly switched between superhydrophobic, Cassie-Baxter state to hydrophilic, Wenzel state by the application of an electric field, especially below a threshold value.

Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Manipulation of magnetic nanostructures through low temperature metal-oxygen chemistry: Co/CoO exchange biased nanodonuts and Co nanotips - Phase, Deodatta; Choudhary, Ram Janay; Ganesan, V.; Reddy, V. Raghvendra; Gupta, Ajay; Selvi, N.; Kulkarni, Sneha; Ogale, Satishchandra (Solid State Communications, 2009)
Dense nanodonut and nanotip type morphologies are shown to self-evolve in Ultrathin cobalt films during growth under Vacuum, depending oil the level of oxygen incorporation and temperature. The nanodonut morphology forms at room temperature and the corresponding magnetic hysteresis shows exchange bias (similar to 35 Oe shift along the field axis), which is attributed to the presence of CoO and its exchange Coupling with cobalt. The morphology evolves into nanotip features with increase of growth temperature, with Concurrent elimination of the oxide component and exchange bias. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Co/CoO; Magnetic film; self assembly; Vacuum evaporation

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.